1999
DOI: 10.1007/bf03343560
|View full text |Cite
|
Sign up to set email alerts
|

Inefficiency of the anticoagulant therapy in the regression of the radiation-induced optic neuropathy in Cushing’s disease

Abstract: Radiation-induced optic neuropathy is a rare complication (prevalence less than 1%) following radiotherapy of the sellar region. However, the vasculopathy in Cushing's disease predisposes to radiation-induced injury. We report the case of a 24-year-old man with Cushing's disease since he was 16. The hormonal study including bilateral inferior petrosal sinus catheterization diagnosed a pituitary right lesion, but imagiology was always negative. He underwent a transsphenoidal microadenomectomy and the pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…However, the success has been limited in patients with radiation injury to the visual pathway. 49 Moreover, RION has been documented to occur in patients receiving anticoagulation therapy for cardiac disease. 50 …”
Section: Treatmentmentioning
confidence: 99%
“…However, the success has been limited in patients with radiation injury to the visual pathway. 49 Moreover, RION has been documented to occur in patients receiving anticoagulation therapy for cardiac disease. 50 …”
Section: Treatmentmentioning
confidence: 99%
“…I have tried both with poor results. Indeed, like Landau and Killer 22 , I have seen a patient who developed RON while taking warfarin for cardiac disease.…”
mentioning
confidence: 99%
“…Treatment for RON, as emphasized in the two articles in this issue of the Journal 1,2 , is disappointing to say the least. Neither systemic corticosteroids nor anticoagulation, both of which seem to be somewhat effective in treating generalized radionecrosis in the CNS 19,20 , are effective in the treatment of RON 11,21,22 . I have tried both with poor results.…”
mentioning
confidence: 99%
“…A similar beneficial effect, however, has not been demonstrated in patients with RON. 14 Kim et al 15 demonstrated in a rat model that ramipril (an angiotensin-converting enzyme inhibitor) significantly modified radiation-induced injury.…”
Section: Sánchez-orgaz Et Almentioning
confidence: 98%